Preclinical Evaluation of [68Ga]Ga-DFO-ZEGFR:2377: A Promising Affibody-Based Probe for Noninvasive PET Imaging of EGFR Expression in Tumors - Maryam Oroujeni; Javad Garousi; Ken G. Andersson; John Löfblom; Bogdan Mitran; Anna Orlova; Vladimir Tolmachev (Cells, 2018)
Radionuclide imaging of epidermal growth factor receptor (EGFR) expression in tumors may stratify patients for EGFR-targeting therapies and predict response or resistance to certain treatments. Affibody molecules, which are nonimmunoglobulin scaffold proteins, have a high potential as probes for molecular imaging. In this study, maleimido derivative of desferrioxamine B (DFO) chelator was site-specifically coupled to the C-terminal cysteine of the anti-EGFR affibody molecule ZEGFR:2377, and the DFO-ZEGFR:2377 conjugate was labeled with the generator-produced positron-emitting radionuclide 68Ga. Stability, specificity of binding to EGFR-expressing cells, and processing of [68Ga]Ga-DFO-ZEGFR:2377 by cancer cells after binding were evaluated in vitro. In vivo studies were performed in nude mice bearing human EGFR-expressing A431 epidermoid cancer xenografts. The biodistribution of [68Ga]Ga-DFO-ZEGFR:2377 was directly compared with the biodistribution of [89Zr]Zr-DFO-ZEGFR:2377. DFO-ZEGFR:2377 was efficiently (isolated yield of 73 ± 3%) and stably labeled with 68Ga. Binding of [68Ga]Ga-DFO-ZEGFR:2377 to EGFR-expressing cells in vitro was receptor-specific and proportional to the EGFR expression level. In vivo saturation experiment demonstrated EGFR-specific accumulation of [68Ga]Ga-DFO-ZEGFR:2377 in A431 xenografts. Compared to [89Zr]Zr-DFO-ZEGFR:2377, [68Ga]Ga-DFO-ZEGFR:2377 demonstrated significantly (p < 0.05) higher uptake in tumors and lower uptake in spleen and bones. This resulted in significantly higher tumor-to-organ ratios for [68Ga]Ga-DFO-ZEGFR:2377. In conclusion, [68Ga]Ga-DFO-ZEGFR:2377 is a promising probe for imaging of EGFR expression.